Inquiry-Based Learning as a Complementary Method in an Integrated English Course - Navas Brenes, César Alberto (2023)
This work presents the results of a study carried out in a team-taught English course at the University of Costa Rica. It is based on the hybrid modality it is intended to design a proposal of a didactic lesson which follows Information and Communications Technology (ICT) and active learning methods. Its innovation relies on a techno-pedagogical element that aims at generating a change from a traditional methodology, in which in-service professors will embrace in the implementation of student-centered teaching strategies to have a more dynamic, enriching, and challenging course. A sample lesson combines the tools of the University of Costa Rica’s virtual platform Mediación Virtual and a series of digital resources to complete the pedagogical framework of the Inquiry-based Model. The results of a brief questionnaire will be analyzed to assess students’ perception on the teaching modality, the implementation of virtual ICT-based activities as well as their opinions on teaching strategies that best fit this course.